Generators and relations for wreath products - Drozd, Yu. A.; Skuratovskii, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
Generators and defining relations for wreath products of groups are given. Under a certain condition (conormality of generators), they are minimal.